Evaluation of the bond between mastic and coarse aggregates - Silva, Hugo Manuel Ribeiro Dias da (2003)
In the last decades, the flexible road pavements have been subjected to the action of a more intense traffic, which has often originated their premature degradation. Among others, to guarantee a better performance of the pavement, it is essential that the bituminous mixtures show an appropriate behaviour in situ for the high solicitations to which they will be submitted. The bituminous mixtures behaviour is evaluated through tests that allow the study of their properties. The bond between the mastic and the coarse aggregates may possibly influence the behaviour of a bituminous mixture in the pavement. Thus, the main aim of this work was the study of the bond between mastic and coarse aggregates, trying not only to contribute to a better knowledge of this property, but also to a better behaviour of the bituminous mixtures in situ. A proceeding to study the mastic composition was developed and mechanical tests were used in order to evaluate the bond between mastic and coarse aggregates, which is determined through the tensile and shear strengths. The results of the mechanical tests were used to evaluate the influence of the mastic binder content on the strength of the bond between mastic and coarse aggregates. In the same tests, it was also observed the main type of failure of the bond between mastic and coarse aggregates.